Woody plant population dynamics in response to climate changes from 1984 to 2006 in Sahel (Gourma, Mali) - Hiernaux, Pierre H.Y.; Diarra, L.; Trichon, V.; Mougin, E.; Soumaguel, N.; Baup, F. (Elsevier, 2009)
The patterns of the changes in woody plant population densities, size and species composition is documented and discussed for 24 rangeland sites monitored from 1984 to 2006 in Gourma (Mali). The sites are sampled along the North–South bioclimatic gradient on each of the main soils and levels of grazing intensity. Site woody plant populations range from extremely sparse on shallow soils, to scattered on sandy soils, to open forest in temporarily flooded clayed soils, and to narrow thickets on hard pans. Three different methods contributed to assess and monitor woody plant density and canopy cover. In the short term woody populations were struck by the 1983–1984 droughts irrespective of their edaphic situation and location along the bioclimatic gradient. Drought induced mortality was not more severe under drier climate within the Sahel gradient but occurred sooner after drought in shallow soils, and with a lag of a year or two on flooded clay soils. No evidences were found of higher mortality rates in stands with history of intense grazing. Although rainfall remained below average for a decade after the drought, active recruitment of woody plants occurred in all sites starting as soon as 1985. Recruitment proceeded by successive cohorts, often with short-living perennial undershrubs and pioneer shrubs settling first. Acacia species were among the first to settle or re-establish, especially on the sites most intensively grazed. The release of competition due to drought induced mortality and to the reduction of herbaceous cover contributed to the success of the recruitment. The species composition change that resulted could first be interpreted as a shift toward a more arid tolerant flora, then some diversification occurred since the mid 1990s that could indicate a possible return to previous composition in the long term, confirming the resilience Sahel vegetation.